Experimental and simulation analysis of energy absorption capacity of 3D printed structure design - Ling, Zachary Xiwen (Nanyang Technological University, 2024)
This study addresses the challenge of enhancing the energy absorption capabilities of traditional honeycomb structures which are widely used for energy absorption due to their high strength-to-weight ratio and unique collapse mechanisms. Current research explores improving energy absorption through various methods such as modifying the geometry of the basic honeycomb structure or taking inspiration from nature. While these approaches are beneficial, there are limitations as to the possibilities of new designs being discovered. This highlights the need for investigating alternative strategies, such as density gradients, to optimize energy absorption in hexagonal honeycombs. To address this gap, the effects of density gradients on energy absorption characteristics of hexagonal honeycomb structures was investigated. This involved the use of finite element simulations being conducted to analyse the stress-strain behaviour and energy absorption of graded structures under compressive loading This project yielded significant findings regarding the impact of density gradients on energy absorption. The results indicate that the specific design of the graded structures used in this project did not lead to improved energy absorption. This can be attributed to two key factors: 1) the lack of progressive collapse observed in the graded structures, and 2) less well-defined plateau regions in their stress-strain curves. These findings suggest that achieving higher energy absorption using density-graded hexagonal honeycombs may require structures with a higher number of cells per layer and lower relative densities within each layer. The findings of this project show factors that should be considered in the design of energy absorbing materials. The study demonstrates the importance of considering collapse mechanisms and stress-strain behaviour when optimizing honeycombs for energy absorption. This work suggests that density gradients can potentially be beneficial, but the design requires careful consideration of cell number and density distribution within the structure. Additionally, this research opens doors for further exploration in areas such as optimizing the design of graded honeycombs and investigating the effects of different cell geometries and loading orientations.